An applicable approach to mitigate pressure rise rate in an HCCI engine with negative valve overlap. (1st January 2020) - Hunicz, Jacek; Mikulski, Maciej; Geca, Michal S.; Rybak, Arkadiusz
Highlights: Assessment of various measures to extend load in HCCI with NVO fuel reforming. Complex PRR mitigation mechanisms narrowed down to their net phasing effects. Late and long combustion is the key primary driver for low PRR. Expansion rate and NVO fuel reforming have a secondary effect. NVO injection and VVA makes PRR control feasible for HCCI without trade-offs. Abstract: Low-temperature combustion in a homogeneous-charge compression-ignition (HCCI) engine offers high thermal efficiency while cutting off emissions. However, HCCI's feasibility is hampered by excessive peak pressure rise rates under high load, causing combustion noise and possible engine damage. This study considers extending the high-load limit in a boosted HCCI engine accommodating variable valve timing and fuel reforming during negative valve overlap. Three techniques are evaluated on a research engine: (i) exhaust valve timing retardation (ii) boost pressure adjustment and (iii) reduction of fuel subjected to reforming. Two load regimes are explored: a mid-load point with indicated mean effective pressure of 0.61 MPa; and high-load conditions achieved by 25% more fuelling. The former is often reported as boundary condition for HCCI's, the latter is usually far beyond the acceptable pressure rise rate limit. Results indicate that strategies (i) and (iii) offer a trade-off-free solution for high-load extension. This can be realized as a supervisory, in-cylinder pressure based, control function. Independently of the pressure rise rate mitigation method considered, two key variables are crucial for closed-loop control: the in-cylinder volume at 50% fuel burnt and the combustion duration. They are closely coupled and can be real-time calculated using well-established control framework based on sensing the combustion timing. The expansion rate and differences in fuel mass subjected to reforming are secondary for pressure rise rate estimation and should be considered if greater accuracy is required.